The sinner - Stevens, Amanda (Novelist) (Don Mills, Ontario : MIRA, 2016)
"I'm a cemetery restorer by trade, but my calling has evolved from that of ghost seer to death walker to detective of lost souls. I solve the riddles of the dead so the dead will leave me alone. I've come to Seven Gates Cemetery nursing a broken heart, but peace is hard to come by ... for the ghosts here and for me. When the body of a young woman is discovered in a caged grave, I know that I've been summoned for a reason. Only I can unmask her killer. I want to trust the detective assigned to the case for he is a ghost seer like me. But how can I put my faith in anyone when supernatural forces are manipulating my every thought? When reality is ever changing? And when the one person I thought I could trust above all others has turned into a diabolical stranger?"--Page 4 of cover.
Keywords: Murder -- Investigation -- Fiction; Cemeteries -- Fiction; South Carolina -- Fiction; Romance fiction; Paranormal fiction